The Effect of Achievement Motivation Training on Achievement Motivation of Students at Islamic Boarding School X in Karanganyar - Lintang Seira; Clarina Putri; Abdul Nizar (At Turots: Jurnal Pendidikan Islam, 2024)
Islamic boarding school students have responsibilities not only in the academic field in general but also religious education. Status as a santri certainly has an impact on understanding religious knowledge and it is not uncommon for santri to be required to memorize the Al-Quran. The diverse backgrounds of the students at Islamic Boarding School X Karanganyar also make the students' motivation to achieve low. This research aims to determine the effect of achievement motivation training on the achievement motivation of students at Pondok Pesantren X in Karanganyar. The method in this research uses a pre-experiment with one group pretest and posttest design. This research involved 65 students at Islamic boarding school X in Karanganyar. The respondents of this study were male and female with an age range of 14-15 years. Hypothesis testing in this research uses Paired Sample T-Test statistical analysis. The results of this study show a difference in mean achievement motivation scores with a significance value of 0.000 (p<0.001) with a t value: -10.874. These results show that the achievement motivation of students at Pondok Pesantren X in Karanganyar increased after being given treatment in the form of achievement motivation training.